Study of plasma fibrinogen level and its relation to glycemic control in type-2 diabetes mellitus patients attending diabetes clinic at a tertiary care teaching hospital in Madhya Pradesh, India - Gupta, Parag; Bhambani, Pawan; Narang, Sanjeev (International Journal of Research in Medical Sciences, 2016)
Background: Diabetes mellitus comprises a group of common metabolic disorders where increased fibrinogen levels can act as a thrombogenic factor. Diabetic patients have higher cardiovascular morbidity than non-diabetic subjects. Several studies have shown that haemostatic factor especially hyperfibrinogenemia is implicated as a source of atherosclerosis and its complications. Methods: A comparative observational study was conducted to compare fibrinogen levels between type 2 diabetes patients and healthy controls. Their fibrinogen levels were compared and co-related with glycemic status and other risk factors and parameters like glycosylated haemoglobin, age, sex, smoking, body mass index (kg/m2), hypertension and ischemic heart disease. Results: It was seen that in the diabetic subset, the plasma fibrinogen levels are significantly higher than the non-diabetic subset (386.04±132.87 vs. 314.38±97.42; p<0.001). Our study re-established correlation between HbA1c and fibrinogen levels of the diabetic patient is positive i.e., poorer the glycemic status, higher the fibrinogen levels (r=0.24). Conclusions: It can be concluded from the study that fibrinogen levels are increased in type 2 diabetic subjects with and without CHD. Plasma fibrinogen levels usually increased in type 2 diabetes, thus suggesting that hyperfibrinogenemia could contribute to the excess cardiovascular morbidity and mortality in this disease.